2020
DOI: 10.2196/14359
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate of Gastric Cancer Patients in Jordan: Secondary Data Analysis

Abstract: Background Gastric cancer accounts for 2.7% of all newly diagnosed cancer cases in Jordan. Objective The aim of this study was to calculate the survival rate and its determinants among Jordanian patients who were diagnosed with gastric cancer between 2010 and 2014. Methods A descriptive study was conducted based on secondary analysis of data from the Jordan Cancer Registry during the period of 2010-2014. Onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…The mean two-year OS for gastric cancer patients in our study was 20.097 months, which is lower compared to previous studies [ 13 , 14 ]. An Iranian study reported one-year, three-year, and five-year median survival rates of 66%, 31%, and 21.60% respectively.…”
Section: Discussioncontrasting
confidence: 86%
“…The mean two-year OS for gastric cancer patients in our study was 20.097 months, which is lower compared to previous studies [ 13 , 14 ]. An Iranian study reported one-year, three-year, and five-year median survival rates of 66%, 31%, and 21.60% respectively.…”
Section: Discussioncontrasting
confidence: 86%
“…Recently, although great advances have been made in clinical therapeutic approaches, the survival rate of GC patients is still very low [ 26 ]. Therefore, it is urgent to search for novel therapeutic targets for GC.…”
Section: Discussionmentioning
confidence: 99%
“…The current consensus is that surgery remains the primary curative approach for gastric cancer. With advancements in surgical technology and the integration of conventional radiotherapy, chemotherapy, and neoadjuvant therapy, the 5-year survival rate for patients with early-stage gastric cancer can reach an impressive 95% [ 1 ], while the 5-year survival rate of patients with advanced gastric cancer is a mere 20–60% [ 4 ]. Retrospective analysis of clinicopathological data from 120 patients with advanced gastric cancer admitted from 2014 to 2016 at Suqian Hospital Affiliated with Xuzhou Medical University was performed.…”
Section: Introductionmentioning
confidence: 99%